A smartphone program to support adherence to oral chemotherapy in people with cancer: Proof‐of‐concept trial. Issue 5 (30th January 2022) - Skrabal Ross, Xiomara; Gunn, Kate M.; Suppiah, Vijayaprakash; Patterson, Pandora; Boyle, Terry; Carrington, Christine; Tan, Shir Ley; Ryan, Marissa; Joshi, Rohit; Olver, Ian
Abstract: Aim: Nonadherence to oral chemotherapy (OC) can lead to health complications, including premature death. Mobile phones are increasingly used to deliver medication adherence interventions. However, there is limited evidence about mobile phone–based interventions to increase adherence to OC, specifically. This study explores the proof‐of‐concept of a smartphone program to support adherence to OC in people with cancer. Methods: This was a 10‐week, nonrandomized, multisite trial. The outcomes assessed were acceptability, satisfaction with the intervention, adherence to OC, knowledge about OC, and side‐effects presence and severity. The program consisted of short message service (SMS) reminders to take OC, as well as information about OC, including the management of side‐effects. Results: Twenty‐two participants (17–74 y/o, median age 60 y/o) were recruited at six hospitals. The sample included 10 different cancer diagnoses (predominance of breast cancer) and 11 OC medications. Acceptability of the intervention was high, with 95% of the enrolled participants completing postintervention measures, and 81% reporting high satisfaction with the program. The intervention was found to have no effect on supporting adherence to OC (assessed by self‐report and medication event monitoring system) in this sample. An increase in knowledge about OC was observed at postintervention ( p  = 0.010). Conclusions: This study demonstrated proof‐of‐concept of the smartphone program and highlighted the need for intervention and trial design‐related refinements. Future work should evaluate the effect of the program on adherence to OC with nonadherent patients. Abstract : Proof‐of‐concept of a smartphone program to support adherence to OC in people with cancer was explored. High acceptability and satisfaction with the intervention were found and the need for intervention and trial design‐related refinements was highlighted.